A final analysis of K1 and K2 1000 m in the Olympic Games in London 2012 kayak - Prendes Garcia-Barrosa, C. M. (Training sprint canoeing. Progress in improving the physical, technical, tactical, psychological and nutritional preparation, 2015)
The goal of the Belgium National Canoeing Team for the Olympic cycle of London 2012 was to qualify for men's K-1 and K-2. Two of the five athletes (Bob Maesen and Wouter D'haene) already had Olympic experience and this was their last chance to compete at this level. The other three kayakists started their Olympic cycle in the under 23's. Olivier Cauwenbergh and Maxime Richard started their Olympic cycle as under 23's European Champions in K-2 1,000 metres, and they came second in K-2 500 metres in 2009. Laurens Rannecoucke came fifth in the K-1 1,000 metres in the Under 23's European Championship of 2010. These facts made them suitable candidates to qualify for London 2012. The original target was fulfilled for the K-2, as they came fourth in the 2011 World Championship (Szeged), achieving a straight pass to the Olympics. Unlike the K-2, the K-1 did not qualify. The two-crew members were Olivier Cauwenberg and Laurens Rannecoucke. In the 2011-2012 season, Maxime Richard, one of the five potential candidates to fight for a spot at the Olympics, qualified at the European competitions in the Olympic play-off on the K-1 200 metres that took place in May. In this event, Wouter D'haene missed his last chance to be an Olympian again and both Maesen and him retired after the 2011 -2012 season. The short number of candidates, the fact that these five athletes belong to two different sport administrations in Belgium (four Flamenco's and a Walloon) with different selection criteria and also different sports policies, their age and experience disparities, their different performance level and distance specialization, made it difficult to decide which crew would fight for the qualification to the 2012 Olympic Games in the K-2 1,000 metres. In October 2010, Olivier Cauwenbergh, Laurens Rannecoucke, Bob Maesen and Wouter D'haene started the selection process to define the K-2 1,000 metres crew that would compete in the World Championship for an Olympic seed. After a trial period of five possible combinations, Olivier-Laurensand Wouter-Bob went through an exhaustive process in the World Cup races to compete for a spot at the World Championships. Olivier and Laurens exhibited their potential in the internal selection showing regularity amongst the best world crews in the K-2 1,000 metres throughout the entire season. This lead the National Team to the 2011 World Championship where they came fourth, qualifying for London 2012.